HIV infection, risk behaviors, and depressive symptoms among Puerto Rican sex workers. - Alegría, M (1994)
This paper examines the association of depressive symptoms with human immunodeficiency virus (HIV) infection and risk behaviors among 127 sex workers. Data were obtained by a structured interview and blood specimens tested for HIV. Findings showed a high prevalence rate of depressive symptoms for all sex workers regardless of HIV infection status. Results of a logistic regression analysis indicated that the use of injected drugs and engaging in unprotected intercourse with clients were strongly associated with a high level of depressive symptoms.